Pengaruh Komitmen Organisasi Terhadap Sistem Informasi Keuangan - Lesi Hertati; Otniel Safkaur (Department of Accounting-Faculty of Economic and Business (FEB), 2020)
The complexity of the financial information system process requires obeying the Indonesian financial accounting standard regulatory procedures in carrying out financial information, as well as demanding that individuals implementing financial information systems have strong working power that is safe and sustainable in order to run a good financial information system process. The purpose of this study is to determine the effect of organizational commitment to financial information systems, on state-owned enterprises in South Sumatra. This research is a quantitative method research with a total sample of 48 BUMN spread across South Sumatra. The analytical tool used is multiple regression with SPSS version 24. The results show that organizational commitment influences financial information systems.